2012
DOI: 10.1038/cdd.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

EphA/ephrin-A signaling is critically involved in region-specific apoptosis during early brain development

Abstract: EphAs and ephrin-As have been implicated in the morphogenesis of the developing brain. We found that EphA7 and ephrin-A5 are coexpressed in the dorsal midline (DM) of the diencephalon and anterior mesencephalon. Interestingly, programmed cell death (PCD) of the neural epithelial cells normally found in this region was reduced in ephrin-A5/ephrin-A2 dual-deficient embryos. In contrast, in vivo expression of ephrin-A5-Fc or full-length ephrin-A5 strongly induced apoptosis in neural epithelial cells and was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 58 publications
6
41
1
Order By: Relevance
“…In addition, the increased sensitivity of axons could induce axon degeneration and the death of the neurons, which normally project their axon through the AC. Indeed, both semaphorins and ephrins have been shown to promote cell death (Park et al, 2013;Vanderhaeghen and Cheng, 2010), and we observed cell death in E14.5 mutant piriform cortex, which is likely to depend on extrinsic factors since mutant neurons do not exhibit increased death in vitro. Alternatively, or in addition, mutant neurons impaired in axon growth might not reach antiapoptotic factors, such as neurotrophic factors expressed at the midline (Barnes et al, 2007;Huang and Reichardt, 2001).…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the increased sensitivity of axons could induce axon degeneration and the death of the neurons, which normally project their axon through the AC. Indeed, both semaphorins and ephrins have been shown to promote cell death (Park et al, 2013;Vanderhaeghen and Cheng, 2010), and we observed cell death in E14.5 mutant piriform cortex, which is likely to depend on extrinsic factors since mutant neurons do not exhibit increased death in vitro. Alternatively, or in addition, mutant neurons impaired in axon growth might not reach antiapoptotic factors, such as neurotrophic factors expressed at the midline (Barnes et al, 2007;Huang and Reichardt, 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Also, genetically mutant mice lacking both JNK1 and JNK2 show less apoptotic cell death at the neural fold edges and a defect in neural tube closure [15]. In ephrin-A5 null mutant embryos, the number of EphA7-expressing cells is significantly increased in the dorsal midline of the diencephalon and mesencephalon [16]. These studies strongly suggest that, in the dorsal midline region of the diencephalon and mesencephalon, neuroepithelial cells transmit robust EphA7/ephrin-A5 signaling at sites of cell-cell contact, and this bi-directional signaling may have a biochemical linkage with the pro-apoptotic pathway (Fig.…”
Section: Expression Of Ephrina5-fc and Epha8-fc Results In Apoptotic mentioning
confidence: 99%
“…Although preclustering ephrinA5-Fc with anti-Fc secondary antibodies enhances its stimulatory effect on EphA receptors, ephrinA5-Fc fusion protein also has a stimulatory effect on EphA receptors without its preclustering [16]. Therefore, it is predicted that ephrinA5-Fc stimulates forward signaling through EphA receptors when its expression is induced in cells expressing both EphA7 and ephrin-A5.…”
Section: Expression Of Ephrina5-fc and Epha8-fc Results In Apoptotic mentioning
confidence: 99%
“…Caspase 3 activation has also been found to coincide with ephrin-induced EphA4 activation, albeit in an apoptotic situation (Park et al, 2013). Although Eph activation-induced apoptosis might play a role during neural development (Depaepe et al, 2005;Duffy et al, 2008), we have demonstrated previously that in EphA3-HEK293 and melanoma cells ephrinA5-induced cell contraction does not induce apoptosis (Lawrenson et al, 2002), indicating that localised caspase-3 activation and PTP-PEST cleavage in ephrin-stimulated EphA3-HEK293 cells reflects one of the non-apoptotic caspase functions that have been previously described (Miura, 2012).…”
Section: A Caspase-cleaved Ptp-pest N-terminal Ptp Fragment Controls mentioning
confidence: 98%